2019
DOI: 10.4049/jimmunol.1801557
|View full text |Cite
|
Sign up to set email alerts
|

Noncanonical Role of FBXO6 in Regulating Antiviral Immunity

Abstract: The evolutionarily conserved F-box family of proteins are well known for their role as the key component of SKP1-Cullin1-F-box (SCF) E3 ligase in controlling cell cycle, cell proliferation and cell death, carcinogenesis, and cancer metastasis. However, thus far, there is only limited investigation on their involvement in antiviral immunity. In contrast to the canonical function of FBXO6 associated with SCF E3 ligase complex, we report, in this study, that FBXO6 can also potently regulate the activation of IFN-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 53 publications
0
33
0
Order By: Relevance
“…F-box proteins were originally identified as a component of the SKP1-Cullin1-F-box (SCF) E3 ligase complex that initiate the ubiquitin-mediated destruction of their specific downstream substrates (25). Extensive studies have indicated that F-box proteins play pivotal roles in multiple cellular processes, such as cell growth and survival, cellular immune response, carcinogenesis, and cancer metastasis (26)(27)(28)(29)(30)(31)(32), through ubiquitylation, and subsequent degradation of target proteins (25,33). Some F-box proteins have been reported to regulate the type I IFN signaling (IFN-I).…”
mentioning
confidence: 99%
“…F-box proteins were originally identified as a component of the SKP1-Cullin1-F-box (SCF) E3 ligase complex that initiate the ubiquitin-mediated destruction of their specific downstream substrates (25). Extensive studies have indicated that F-box proteins play pivotal roles in multiple cellular processes, such as cell growth and survival, cellular immune response, carcinogenesis, and cancer metastasis (26)(27)(28)(29)(30)(31)(32), through ubiquitylation, and subsequent degradation of target proteins (25,33). Some F-box proteins have been reported to regulate the type I IFN signaling (IFN-I).…”
mentioning
confidence: 99%
“…FBXO44 Mediates BRCA1 Ubiquitination and protein metabolism 50 . The activation of IFN-I signaling can be reversed by the FBXO6 51 . Our analysis further discovered that antigen processing (Ubiquitination & Proteasome degradation) and mRNA Splicing are involved in the SARS-CoV-2 infection by analyzing the Reactome Pathway Database.…”
Section: Discussionmentioning
confidence: 99%
“…There are limited studies describing a role for FBXO6 in the immune system (14,15). In one study, investigators found that in the context of experimental viral infection, FBXO6 targeted the interferon regulatory factor 3 (IRF3) for degradation (14).…”
Section: Discussionmentioning
confidence: 99%
“…There are limited studies describing a role for FBXO6 in the immune system (14,15). In one study, investigators found that in the context of experimental viral infection, FBXO6 targeted the interferon regulatory factor 3 (IRF3) for degradation (14). The authors proposed that FBXO6 degradation of IRF3 functioned to limit the antiviral response by down-regulating interferon signaling and prevent damage by an overactive antiviral response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation